Sexueller Missbrauch und Gewalt: Wege zu hohen Anerkennungsleistungen und Entschädigungen - Jaeger, Lothar (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
Sexual abuse of altar servers and rape of young girls and women were committed in both churches. The victims suffered not only physically, but also psychologically. They are entitled to particularly high compensation for pain and suffering, which the book provides instructions on how to calculate. Those affected and their lawyers will find out against whom claims should be made and what substantiated evidence of abuse and psychological damage is absolutely necessary. Material damage must also be compensated. Loss of earnings can be claimed after decline of school performance. Psychological damage can lead to early incapacity to work and also trigger household management damage and pension damage.